Systemic inflammation and symptom severity in patients with advanced cancer: a prospective study. (1st April 2011) - Haworth, G; Rush, R; Fallon, M; Laird, B
Abstract : Abstract: Aim: Pain, depression, fatigue and nausea are common symptoms in cancer and can cause significant physical and psychological distress. In non-malignant conditions, systemic inflammation is implicated in the genesis of these symptoms. The relationship between inflammation and these symptoms in cancer is less clear. The aim of this study was to examine the relationship of systemic inflammation and pain, fatigue, depression and nausea/vomiting in patients with advanced cancer. Methods: An observational, cross-sectional study conducted in a specialist palliative care unit. All cancer patients admitted over a 3 month period were assessed. Eligible patients had assessments of inflammation (C reactive protein (CRP) and albumin) and symptoms (ESAS). A bivariate statistical analysis was conducted. Results: 64 patients were assessed with 50 being eligible. Significant correlations (Spearman) were found for pain (0.343, p=0.015) and depression (0.357, p= 0.011) with CRP. No significant correlations were found for fatigue (0.020, p=0.890) and nausea/vomiting (0.276, p=0.052). No significant associations were found for any symptom and serum albumin. Conclusion: Systemic inflammation is related to pain and depression in cancer. Such a relationship may provide a therapeutic opportunity for specific anti-inflammatory therapy that improved pain and depression. Further work examining this relationship would be of interest.